Implementing a cohesive programming ecosystem in mechanical engineering - Oster, Zakary Christian (Kansas State University, 2024)
The ability to apply modern solution methods is critical for the success of mechanical engineers. While handwritten solutions were once the state of the art, computer programs provide unparalleled power and speed to solve problems. Because of this, it is critical that academic curriculum teaches students to use programming to solve problems. The current implementation of programming in the Department of Mechanical Engineering at K-State varies, with three different languages being used. The usage rate also varies, with many classes failing to take advantage of the tools provided by programming, and this is reflected by the ability and confidence of students in the department. This project demonstrates the possibility of using one programming language and environment through the mechanical engineering undergraduate curriculum. The completed projects and assignments showcase the use of Python, the Raspberry Pi Pico, Visual Studio Code, and Jupyter Notebooks as they relate to problem-solving in the field of mechanical engineering.
Keywords: Python; Programming; Curriculum; Cohesive; Problem solving; Redesign